A User-Friendly Tool to Characterize the Moisture Transfer in Porous Building Materials: FLoW1D - Virginia Cabrera; Rubén López-Vizcaíno; Ángel Yustres; Miguel Ángel Ruiz; Enrique Torrero; Vicente Navarro (Applied Sciences, 2020)
This paper presents a user-friendly tool—FLoW1D (One-Dimensional Water Flow)—for the estimation of parameters that characterize the unsaturated moisture transfer in porous building materials. FLoW1D has been developed in Visual Basic for Applications and implemented as a function of the well-known Microsoft Excel© spreadsheet application. The aim of our work is to provide a simple and useful tool to improve the analysis and interpretation of conventional tests for the characterization of the hygric behavior of porous building materials. FLoW1D embraces the conceptual model described in EN 15026 for moisture transfer in building elements, and its implementation has been verified and validated correctly. In order to show the scope of the code, an example of an application has been presented. The hygric characterization of the limestone that is mostly employed in the Cathedral of Santa Maria and San Julian in Cuenca (Spain) was conducted based on an analysis of the conventional water absorption by capillarity tests (EN 15801).